Theory in Determining Good and Bad in Human Actions - Zaskia Adea Mika; Paujianur; Fatimatus Azahra Putri; Dita Riani; Ajahari (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
The concepts of good and bad are essential in understanding human behavior and the moral values that govern society. These concepts are often used as benchmarks to evaluate an individual’s actions and determine whether such actions are socially acceptable. They have been integral to human life since ancient times and continue to develop alongside changes in social, cultural, and religious contexts. In daily life, individuals frequently encounter situations that require moral judgment; therefore, understanding the concepts of good and bad is crucial for making appropriate decisions and behaving in accordance with established moral values. Moreover, these concepts influence our relationships with society and those around us, shaping personal identity and character. Throughout history, various philosophers and ethicists have proposed theories to explain how the concepts of good and bad are formed and how they can guide moral decision-making. Among the most prominent are consequentialism, deontology, and virtue ethics. This journal discusses the theories and concepts of good and bad in relation to human actions and examines their practical application in everyday life. Understanding these concepts can enhance moral awareness and support better decision-making in various situations. In addition, this paper explores how factors such as culture, religion, and personal experience contribute to shaping individuals’ perceptions of good and bad. Thus, this journal aims to provide a deeper understanding of these moral concepts and their relevance to human behavior. It is also expected to serve as a reference for readers who wish to further study ethical theories and the foundations of moral evaluation.